2020
DOI: 10.1507/endocrj.ej19-0245
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes in neonatally X-irradiated thyroid gland in rats

Abstract: Exposure to ionized radiation in childhood has been recognized as a risk factor for the development of thyroid cancer and possibly for other thyroid disorders. However, the effects of neonatal radiation exposure on thyroid morphology and functions have never been explored despite its potential importance. One-week-old male Wistar rats were subjected to cervical X-irradiation at 6 and 12 Gy. Animals were examined at the ages of 2, 8 and 18 weeks old. For comparison, 8-weekold rats were cervically X-irradiated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Serum TSH levels were significantly increased in irradiated neonatal rats. It has been suggested that epithelial height is inversely related to serum TSH levels 7 . However, in this study, the serum TSH level was only slightly increased in 4W rats compared to that in the control at 6 months post-irradiation, and this change was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum TSH levels were significantly increased in irradiated neonatal rats. It has been suggested that epithelial height is inversely related to serum TSH levels 7 . However, in this study, the serum TSH level was only slightly increased in 4W rats compared to that in the control at 6 months post-irradiation, and this change was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The five largest thyroid follicles from each field of view were selected for measurement. The epithelial height and colloid area were measured using the BZ-II Analyzer software (Keyence Co.) as described previously 7 . The first and second layers of follicles from the outside were defined as the peripheral zone, while the other area was defined as the central zone 34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laboratory investigations with animal models have rarely been conducted to understand the underlying mechanisms. We recently demonstrated that the thyroid in rats X-irradiated at the age of 5–6 days developed the specific morphological changes characterized by smaller-sized follicles 15 . In the present study, we further investigated this model to understand the impacts of neonatal irradiation on the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies to investigate the underlying mechanisms in animal models have rarely been performed 14 . Previously, we cervically X-irradiated 5–6 days old Wistar rats and, after comparing them with rats irradiated at 8 weeks old, found that thyroid follicle sizes were reduced only after the neonatal irradiation 15 . In the present study, we further investigated this animal model by examining the effects at different radiation doses and ages.…”
Section: Introductionmentioning
confidence: 94%